Students’ perceptions on native English-speaking teacher in EFL teaching - Prayogi, Duta; Widiyati, Elok (CV. Yudhistt Fateeh, 2024)
English is mostly used by people throughout the world because of its role as an international language. This situation makes many non-English language speaking countries apply English Language Teaching (ELT). The existence of Native English-Speaking Teacher (NEST) then becomes an alternative way to create better atmosphere in language teaching. This research revealed how actually the students’ perceptions toward the existence of NEST in ELT at the school. As the descriptive quantitative research, this research used questionnaire as the main instrument and interview as the supplemental instrument. The subjects of this study were the eleventh-grade students from a public vocational school. The students’ perceptions in this research were classified into 3 aspects. They were students’ perceptions toward NEST’s teaching, NEST’s strengths and weaknesses, and NEST’s behaviour. The research found that they perceived the NEST’s teaching was not understandable but they still could follow his explanation in some particular points. The students also perceived that the NEST was good in developing positive attitudes through his teaching, his confidence in using English, and his original accent. In another hand he was not really good in understanding the students’ culture and he could not use the students’ first language. Finally, they perceived that the NEST was a disciplinarian and strict teacher. However, he was perceived as a friendly and humorous person who totally used English in the class. and used various teaching materials.